PENGARUH KHOTBAH ALKITABIAH DARI PENGKHOTBAH TERHADAP INTENSITAS BERIBADAH - Robertus Suryadi (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2022)
The main points relating to the preacher and the intensity of worship examined in this article include the personality and exemplary attitude of the preacher, mastery of the sermon material, interpretation of the sermon and discussion, the application of the text in the sermon in line with the context of the text and relevant to current life and appropriate use , the truth of the word delivered motivates the congregation towards the intensity of the church moved by the truth of the word delivered. The next explanation in this article is a description of the thoughts of church leaders about the importance of preaching the word and worship of Christianity. In accordance with the existing problems, the purpose of writing this scientific work is: First, to analyze and interpret the preacher for the preaching of the word. Second, to discuss how the personality of the preacher influences the content of sermons worshiped in the lives of believers today. In writing this scientific paper, the writer uses quantitative research methods.